A mancha farinhosa do feijoeiro comum - Vieira, Clibas; Shands, Henry (Revista Ceres, 1965)
A rarely-encountered foliar disease of beans (Phaseolus vulgaris), floury leaf spot, is reported for the 3rd time in 31 years in the vicinity of Vigosa, Minas Gerais, Brazil. The causative fungus, Ovularia phaseoli Drum. (Ramularia phaseolina Petr.). produces a floury, white growth on the undersurface of the leaves. It is not considered to be economically important, although the principal bean variety of the area, Rico-23, is susceptible.